Synthesis and Characterization of Some New Phthalides - Kukreti, V.; Chamoli, R.P. (Asian Journal of Chemistry, 2010)
A series of some new phthalides has been synthesized by condensing a γ-oxoacid, 2-(2,5-dichlorobenzoyl) benzoic acid with various mono, di and trihydroxyphenols in presence of concentrated sulphuric acid.